The Influence of Nanodiamonds and Aluminum Oxide Nanoparticles on the Structure and Properties of High-Strength Concrete - Beskopylny, Alexey N.; Özkılıç, Yasin Onuralp; Stel’makh, Sergey A.; Shcherban’, Evgenii M.; Elshaeva, Diana; Chernil’nik, Andrei; Madenci, Emrah; Aksoylu, Ceyhun (Civil Engineering Journal, 2025)
High-performance concrete (HPC) is an important construction material that can be improved with nano-additives. In this study, the modification of HPC with KHA-HC nanodiamond and nano aluminum oxide (NA) admixtures was investigated; the admixture rate was applied in the range of 0-1.4% in 0.2% increments. The rheology, density, compressive and flexural strength, water absorption, and microstructure properties were investigated; the results showed that the KHA-HC nanodiamond showed higher efficiency than NA. Compared with HPC without nano-additives, the strength properties of HPC with the most optimal content of nano-additives, 0.6% KHA-HC and 1.0% NA, were improved by 47.1% and 17.0% for compressive strength and by 44.9% and 16.3% for flexural strength. Water absorption decreased by 33.0% and 26.0%, respectively. Also, with optimal dosages of nano-additives, an improvement in the rheology of the HPC mixture was recorded. The complex modification of HPC 0.6% KHA-HC and 1.0% NA provides a synergistic effect and maximum improvements in properties: the increase in compressive strength was 58.2%; flexural strength - 54.1%; decrease in water absorption - 49.1%. HPC modified by nano-additives has an improved macro- and microstructure. The two types of nano-additives’ effectiveness, KHA-HC and NA, both separately and together in HPC technology for additional improvement of their operational properties, has been proven.